Metformin Administration During Early Postnatal Life Rescues Autistic-Like Behaviors in the BTBR T+ Itpr3tf/J Mouse Model of Autism - Wang, Lian; Cai, Yulong; Fan, Xiaotang (Frontiers in Behavioral Neuroscience, 2018)
Autism spectrum disorder (ASD) is a developmental disorder that is characterized by the impairment of social interactions, restricted interests, and repetitive behaviors. Although the global incidence of ASD has increased over time, the etiology of ASD is poorly understood, and there is no effective pharmacological intervention for treating ASD. Recent studies have suggested that metformin has the potential to treat ASD. Thus, in the present study, we investigated the therapeutic effects of early metformin treatment on the BTBR T+ tf/J (BTBR) mouse model of ASD. We observed that early metformin administration significantly reversed social approach deficits and reduced repetitive self-grooming and high marble burying scores in BTBR mice. Metformin did not change the general locomotor activity or anxiety-like behavior in both BTBR and C57BL/6J (B6) mice. Our findings suggest that early metformin treatment may have therapeutic efficacy for treating behavioral deficits in autism.